PENGARUH FAKTOR KEPRIBADIAN TERHADAP MINAT BERWIRAUSAHA PADA SISWA KELAS XI PROGRAM KEAHLIAN PEMASARAN DI SMKN 2 BUDURAN SIDOARJO - SHOLIKHA, NOVIATUS (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
In the global era, the world faced the situation where the changes will occur rapidly in all aspects of human life. One of the schools offer special education is vocational. The purpose of CMS is preparing to enter graduate employment and to develop a professional attitude within the scope of business and management expertise. Each student has an entrepreneurial behavior and personality factors more than the other, so that students are able to be independent, creative, have a desire achievement, dare to risk giving rise to interest in entrepreneurship in order to create jobs even advance a nation. The purpose of this study was to determine factors determine how much influence the personality of the interest in entrepreneurship in class XI marketing skills program at SMKN 2 Buduran. This research includes associative research uses a quantitative approach. The design in this study is causal research. The population in this study was a class XI student of marketing skills program at SMKN 2 Buduran. In this study, the entire population of 66 respondents was used as a sample, this is determined by using a saturation sampling. Analysis of the data used in this study is multiple regression analysis. These results indicate that personality factors significantly influence berwirusaha interest of 56.2%. Keywords : Personality Factor, Interests of Entrepreneurship.